Building Digital Ethics in the Perspective of Islamic Religious Education - Setiawan, Ikhsan; fadloli; Abdul Chalim; Astrifidha Rahma Amalia (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
This article aims to explore the role of Islamic Religious Education (Islamic Religious Education or PAI) in building digital ethics among the younger generation in the modern era. Using a qualitative-descriptive approach, the study analyzes literature and current social phenomena to identify ethical challenges and Islamic perspectives on digital behavior. The findings reveal that digital media has created new ethical dilemmas, including the rise of hoaxes, cyberbullying, hate speech, and moral decline among youth. Islamic ethical principles such as adab, honesty, tabayyun, and responsibility are central in addressing these issues. The discussion emphasizes the need for Islamic education to integrate digital literacy and contemporary ethical discourse into its curriculum and teaching strategies. The study concludes that PAI has a vital impact in shaping ethical digital behavior and offers a spiritual framework for navigating the complexities of online interaction. Strengthening digital ethics through Islamic education can foster a more civil, responsible, and moral digital culture